Effects of the STAMP-inhibitor asciminib on T cell activation and metabolic fitness compared to tyrosine kinase inhibition by imatinib, dasatinib, and nilotinib - Häselbarth, Lukas; Karow, Axel; Mentz, Kristin; Böttcher, Martin; Roche-Lancaster, Oisin; Krumbholz, Manuela; Jitschin, Regina; Mougiakakos, Dimitrios; Metzler, Markus (Cancer Immunology, Immunotherapy, 2023)
T cell function is central to immune reconstitution and control of residual chronic myeloid leukemia (CML) cells after treatment initiation and is associated with achieving deep molecular response as a prerequisite for treatment-free remission, the ultimate therapeutic goal in CML. ATP-pocket-binding tyrosine kinase inhibitors (TKIs) like imatinib, dasatinib, and nilotinib are widely used for treating CML, but they have shown to inhibit T cell function as an “off-target” effect. Therefore, we tested asciminib, the first-in-class BCR::ABL1 fusion protein inhibitor specifically targeting the ABL myristoyl pocket (STAMP) and compared its effects on T cell function with imatinib, dasatinib, and nilotinib. Whereas all four TKIs inhibited the expression of the co-stimulatory protein CD28, the amino acid transporter CD98, proliferation, and secretion of pro-inflammatory cytokines IFNγ, IL-6, and IL-17A upon T cell stimulation, asciminib had less impact on PD-1, activation markers, and IL-2 secretion. T cells treated with asciminib and the other TKIs maintained their ability to mobilize their respiratory capacity and glycolytic reserve, which is an important surrogate for metabolic fitness and flexibility. Overall, we found milder inhibitory effects of asciminib on T cell activation, which might be beneficial for the immunological control of residual CML cells.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Activity; Asciminib; CML; Metabolism; T cell; TKI

Plasma Metabolome Profiling for the Diagnosis of Catecholamine Producing Tumors - März, Juliane; Kurlbaum, Max; Roche-Lancaster, Oisin; Deutschbein, Timo; Peitzsch, Mirko; Prehn, Cornelia; Weismann, Dirk; Robledo, Mercedes; Adamski, Jerzy; Fassnacht, Martin; Kunz, Meik; Kroiss, Matthias (Frontiers in Endocrinology, 2021)
Context: Pheochromocytomas and paragangliomas (PPGL) cause catecholamine excess leading to a characteristic clinical phenotype. Intra-individual changes at metabolome level have been described after surgical PPGL removal. The value of metabolomics for the diagnosis of PPGL has not been studied yet. Objective: Evaluation of quantitative metabolomics as a diagnostic tool for PPGL. Design: Targeted metabolomics by liquid chromatography-tandem mass spectrometry of plasma specimens and statistical modeling using ML-based feature selection approaches in a clinically well characterized cohort study. Patients: Prospectively enrolled patients (n=36, 17 female) from the Prospective Monoamine-producing Tumor Study (PMT) with hormonally active PPGL and 36 matched controls in whom PPGL was rigorously excluded. Results: Among 188 measured metabolites, only without considering false discovery rate, 4 exhibited statistically significant differences between patients with PPGL and controls (histidine p=0.004, threonine p=0.008, lyso PC a C28:0 p=0.044, sum of hexoses p=0.018). Weak, but significant correlations for histidine, threonine and lyso PC a C28:0 with total urine catecholamine levels were identified. Only the sum of hexoses (reflecting glucose) showed significant correlations with plasma metanephrines. By using ML-based feature selection approaches, we identified diagnostic signatures which all exhibited low accuracy and sensitivity. The best predictive value (sensitivity 87.5%, accuracy 67.3%) was obtained by using Gradient Boosting Machine Modelling. Conclusions: The diabetogenic effect of catecholamine excess dominates the plasma metabolome in PPGL patients. While curative surgery for PPGL led to normalization of catecholamine-induced alterations of metabolomics in individual patients, plasma metabolomics are not useful for diagnostic purposes, most likely due to inter-individual variability.
CRIS-Team Scopus Importer:2021-10-01
Keywords: adrenal; catecholamines; feature selection; machine learning; mass spectronomy; paraganglioma; pheochromocytoma; targeted metabolomics

The Cytogenetic Landscape of Pediatric Chronic Myeloid Leukemia Diagnosed in Chronic Phase - Karow, Axel; Göhring, Gudrun; Sembill, Stephanie; Lutterloh, Friederike; Neuhaus, Fina; Callies, Sara; Schirmer, Elke; Wotschofsky, Zofia; Roche-Lancaster, Oisin; Suttorp, Meinolf; Krumbholz, Manuela; Metzler, Markus (Cancers, 2022)
Philadelphia chromosome-positive chronic myeloid leukemia (CML) is cytogenetically characterized by the classic translocation t(9;22)(q34;q11), whereas additional non-Philadelphia aberrations (nPhAs) have been studied extensively in adult patients with CML, knowledge on nPhAs in pediatric patients with CML is still sparse. Here, we have determined nPhAs in a cohort of 161 patients younger than 18 years diagnosed with chronic phase CML and consecutively enrolled in the German national CML-PAED-II registry. In 150 cases (93%), an informative cytogenetic analysis had been performed at diagnosis. In total, 21 individuals (13%) showed nPhAs. Of these, 12 (8%) had a variant translocation, 4 (3%) additional chromosomal aberrations (ACAs) and 5 (3%) harbored a complex karyotype. Chromosome 15 was recurrently involved in variant translocations. No significant impact of the cytogenetic subgroup on the time point of cytogenetic response was observed. Patients with a complex karyotype showed an inferior molecular response compared to patients carrying the classic translocation t(9;22)(q34;q11), variant translocations or ACAs. No significant differences in the probability of progression-free survival and overall survival was found between patients with nPhAs and patients with the classic Philadelphia translocation only. Our results highlight the distinct biology of pediatric CML and underline the need for joint international efforts to acquire more data on the disease pathogenesis in this age group.
CRIS-Team Scopus Importer:2022-04-08
Keywords: additional chromosomal aberrations; chronic myeloid leukemia; complex karyotype; cytogenetic response; molecular response; pediatric chronic myeloid leukemia; Philadelphia chromo-some; tyrosine kinase inhibitor treatment; variant translocations